Self-Care Experiences of Individuals with Heart Failure: A Systematic Review and Metasynthesis - Israr Ahmad; Agata Bielecka-Dabrowa; Brunilda Subashi; Yi Chen (Journal of Clinical Medicine, 2026)
Background: Heart failure (HF) is a complex, life-threatening syndrome associated with substantial morbidity and mortality, reduced functional capacity, diminished quality of life, and considerable healthcare costs. Globally, HF affects more than 64 million individuals. Chronic heart failure (CHF) imposes a significant economic and personal burden on individuals, society, and the healthcare system, and places substantial demands on effective self-care. Objective: The purpose of this metasynthesis was to explore the self-care experiences of individuals with heart failure and the ways in which they manage their self-care. Methods: A comprehensive search was conducted from January 2014 to July 2025 across four major databases: PubMed/MEDLINE, Web of Science (Clarivate), Scopus, and ProQuest, and two gray-literature sources, OpenGrey and OAIster. A total of 320 records were exported to the Rayyan Systematic Review Management Platform, and after the screening process, only 19 were included for data extraction. The quality of included studies was assessed, and the data were synthesized using thematic synthesis. Results: Three overarching analytical themes were generated that capture multifaceted experiences of individuals living with heart failure and engaging in self-care. These included: adaptive and technology-supported self-management in daily life, emotional and psychological dimensions of self-care, and social, cultural, and environmental influences on self-care. Conclusion: Heart failure self-care is a dynamic and multifaceted process shaped by adaptive daily practices, emotional and psychological experiences, and social and cultural contexts. Individuals continuously adjust behaviors, manage symptoms through lived experience, and rely on supportive relationships and resources to sustain self-care. Recognizing this complexity is essential for developing individual-centered, culturally sensitive interventions that align with the lived realities of individuals with heart failure.